2011
DOI: 10.1097/prs.0b013e318230c2f6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of 331 Consecutive Immediate Single-Stage Implant Reconstructions with Acellular Dermal Matrix

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
189
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(201 citation statements)
references
References 0 publications
6
189
2
4
Order By: Relevance
“…Using this technique, postoperative pain appears to be reduced and recovery is faster. Results are promising, with a complication rate comparable, if not superior to published series of subpectoral implant reconstruction with lower pole ADM coverage [8][9][10][12][13][14] and good aesthetic outcomes. The limited number of complications observed, despite adopting a new technique, may be explained by our previous extensive experience with the use of ADMs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Using this technique, postoperative pain appears to be reduced and recovery is faster. Results are promising, with a complication rate comparable, if not superior to published series of subpectoral implant reconstruction with lower pole ADM coverage [8][9][10][12][13][14] and good aesthetic outcomes. The limited number of complications observed, despite adopting a new technique, may be explained by our previous extensive experience with the use of ADMs.…”
Section: Discussionmentioning
confidence: 70%
“…Techniques have evolved from 2-stage complete submuscular placement of tissue expander (TE), 6,7 to single-stage direct to implant (DTI) reconstruction using partial submuscular coverage and an ADM to cover the lower part of the implant. [8][9][10] Excellent cosmetic outcomes can be achieved as the ADM facilitates natural ptosis and definition of the inframammary fold. Despite this, there are problems with subpectoral implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jordan et al [7] reported that such an increase in the occurrence of seroma multiplied the chance of tissue expander removal by 4.42 times and of infection-induced tissue expander removal by 6.71 times [12]. However, other studies reported no significant association between the use of ADM and seroma formation [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Data from meta-analyses have revealed slightly higher rates of seroma, infection and flap necrosis for HADM-assisted reconstructions compared with traditional, non-HADM-assisted techniques (110,111), although pooling of early results from multiple surgeons' initial experiences with the product may have biased the results (112). More recent studies have demonstrated that with judicious patient selection and precise intraoperative technique (113,114), superior aesthetic results can be achieved with a safety profile that is comparable with or superior to (115) reported series of traditional, non-HADM-assisted approaches (116)(117)(118). Certain questions surrounding HADM-assisted reconstruction have not yet been definitively answered, particularly whether the use of HADM results in reduced postoperative pain, shorter hospital stays and reduced expander fill times compared with traditional techniques (119,120).…”
Section: What Is the Role Of Acellular Dermal Matrix In Implantmentioning
confidence: 99%